2019
DOI: 10.1155/2019/9379864
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of the Aberrant Epigenetic Alteration of Pancreatic Ductal Adenocarcinoma

Abstract: Background. Pancreatic ductal adenocarcinoma (PDAC) remains one of the most fatal malignancies due to its high morbidity and mortality. DNA methylation exerts a vital part in the development of PDAC. However, a mechanistic role of mutual interactions between DNA methylation and mRNA as epigenetic regulators on transcriptomic alterations and its correlation with clinical outcomes such as survival have remained largely uncovered in cancer. Therefore, elucidation of aberrant epigenetic alteration in the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Besides, a decrease in the expression of TRIM58 via hypermethylation has been strongly associated with cancer progression in patients with early stage lung adenocarcinoma ( Kajiura et al, 2017 ). Xu et al (2019) demonstrated that MeDEGs such as TRIM58 exerts great distinct influence on the development of pancreatic cancer via bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a decrease in the expression of TRIM58 via hypermethylation has been strongly associated with cancer progression in patients with early stage lung adenocarcinoma ( Kajiura et al, 2017 ). Xu et al (2019) demonstrated that MeDEGs such as TRIM58 exerts great distinct influence on the development of pancreatic cancer via bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Demokan et al (7) reported that aberrant methylation of CpG islands upstream of this gene was associated with head and neck squamous cell carcinoma (HNSCC). Furthermore, one study recently revealed that the NOL4 gene plays a role in glioblastoma multiform (GBM) (15). NOL4 intronic mutation has been detected in Indian families with Van der Woude syndrome (20).…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Ueki et al ( 13) identified novel nucleolar protein, termed NOLP (Nucleolar Localized Protein) which is now known as nucleolar protein 4 (NOL4). In spite of a number of different studies on the role of NOL4 as a tumor suppressor gene in different types of cancer like squamous cell carcinoma of head and cervical cancer, cervical cancer and Pancreatic ductal adenocarcinoma (7,14,15), there has been no study on the role of this gene in thyroid cancers to date.…”
Section: Introductionmentioning
confidence: 99%
“…It must be added that all the genetic, metabolic and tissue changes produced in tumor cells cause patients to present a great variety of molecular alterations, mutations and aberrations in the expression of different antigens. These variations make it even more difficult to validate a single marker or battery of markers in the diagnosis of pancreatic cancer ( 69 ). The ideal scenario would be the combination of other markers that allows us to detect initial stages.…”
Section: Serological Markers and Ca19-9mentioning
confidence: 99%